Defining 'seasoning' for the coffee sciences - Pe, Vincent Samuel T. (Animo Repository, 2022)
Coffee is a popular drink and it has become increasingly popular for consumers to make their own coffee at home. An important aspect of this is grinding the roasted coffee beans to make the brewed coffee. However, store-bought grinders usually have harsh angles and are very sharp. This causes inconsistent grind sizes. Seasoning is a concept that refers to the technique of breaking in grinders by grinding a large amount of coffee beans to dull the blades to get more consistent coffee. However, there have been no studies which confirm whether seasoning actually does this. This paper aims to resolve this by relating the particle size of the coffee grounds to the amount of coffee processed in the grinder which will verify this concept. To do this, 150 grams of coffee beans were ground in 15 gram batches in 6 coffee grinders. Three of these were identical ceramic conical burr grinders while the other three were stainless steel conical burr grinders. Afterwards, the samples were taken to a laser diffraction analyzer to measure their particle size distributions as well as scanning electron microscopy energy-dispersive X-ray spectroscopy to determine their composition. It will then be checked if there is a noticeable difference between the particle size distributions or if there are abnormal particles present. In terms of particle size, the coffee grounds coming from the ceramic grinders had higher deviations when compared to those coming from the stainless steel grinder. Neither of these grinders showed a decrease in average particle size. The particle size distributions’ ranges started from the 10 to 20 µm mark and ended at the 1500 to 1600 µm area. Almost all of the distributions were identical in shape and did not show any signs of being narrower. More data is needed to verify the claims of seasoning from the perspective of SEM-EDS. The results show that at this scale, seasoning does not have an effect on the coffee’s particle size. Keywords: seasoning, coffee grinders, particle size analysis